EVALUASI PELAKSANAAN SISTEM DAN PROSEDUR PENGELOLAAN PENGELUARAN KAS TERHADAP UANG PERSEDIAAN (UP) SELAMA MASA PANDEMI COVID-19 PADA DINAS PEMUDA DAN OLAHRAGA PROVINSI KALIMANTAN TIMUR - Ida Rahmawati3, Meliana Said1 Imam Nazarudin Latif2 (EKONOMIA, 2021)
The purpose of this writing is to find out and analyze the implementation of Government Regulation (PP) No.12 of 2019 and Regulation of the Minister of Home Affairs (Permendagri) No.77 of 2020 in the implementation of Cash Expenditure Management Systems and Procedures Against Supply Money (UP) during the Covid-19 pandemic at the Youth and Sports Service of East Kalimantan Province. This research is a qualitative descriptive study, with the PP No.12 of 2019 and Permendagri No.77 of 2020 as analysis tools.            The results of the evaluation of the implementation of cash disbursement management systems and procedures for supply money (UP) during the Covid-19 pandemic period at the East Kalimantan Provincial Youth and Sports Office through the implementation stages as regulated in PP No.12 of 2019 and Permendagri No.77 In 2020 and hypothesis testing, it can be concluded that the hypothesis is accepted, which means that the results of the evaluation of the system and procedures for managing cash disbursements against money supply (UP) during the Covid-19 pandemic period at the East Kalimantan Provincial Youth and Sports Office are in accordance with PP No. Number 77 of 2020.